BOOK REVIEW: Michael Weiss, Hassan Hassan, “Isis. Armata Jihadului (Isis: Inside the Army of Terror)”, București, Editura Corint, 2016, 346 p. - LAKATOS, Arthur (Studia Universitatis Babeș-Bolyai Historia, 2017)
After 9/11, the book market was practically “invaded” by works concerning the Al-Qaeda, and the same is happening now in the case of ISIS. Some of these works were (and are) poorly written, sensation-seeking compilations, while others are based on serious documentation. Generally speaking, when a subject is “trending” the possibility to reach academic quality seriously decreases. Considering all of these aspects, the two authors of the present book did their best to create a work which is not only easy to read, but also a valuable source and a comprehensive synthesis of the history of ISIS. Although the book itself has some lacunae in its thematic approach - which can be improved in future editions – my general conclusion is that it represents a well-written analysis; it is well documented with original sources and can be very useful in getting to know the organization which shocked the world with its cruelty and efficiency. Michael Weiss is, first of all, a specialist in the post-Soviet world, having published a series of high quality articles in press products like Foreign Policy and Daily Beast. Starting with 2011, he became a field correspondent transmitting the riots from Syria, getting acquainted with the depths of Middle Eastern politics. His co-author, Hassan Hassan, is a local intellectual, working as a journalist for the National from Abu Dhabi. Co-opted by Weiss, Hassan also has the quality of having been born in Abu Kamal, a town situated on the Iraqi border with Syria, part of the battlefield where, after the demise of Saddam’s Baathist regime, different Arab and international forces are disputing the supremacy of their strategic interests.